THE EFFECT OF EMPLOYEES KNOWLEDGE MANAGEMENT, TIME MANAGEMENT AND WORK MOTIVATION ON ORGANIZATIONAL EFFECTIVENESS AT PT BANK SULUTGO KAWANGKOAN BRANCH - Torongkang, Andre Marsel; Kindangen, Paulus; Rogi, Mira Helen (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
The primary objectives of this research are fourfold: firstly, to know the Effect of Employees Knowledge Management on Organizational Effectiveness at PT Bank SulutGo Kawangkoan Branch; secondly, to know the Effect of Time Management on Organizational Effectiveness at PT Bank SulutGo Kawangkoan Branch; thirdly to know the Effect of Work Motivation on Organizational Effectiveness at PT Bank SulutGo Kawangkoan Branch; and fourthly, to know the Effect of Employees Knowledge Management, Time Management, and Work Motivation on Organizational Effectiveness at PT Bank SulutGo Kawangkoan Branch. The research adopts a quantitative approach, involving whole population or saturation sample of 33 respondents consisting all of employees. Multiple linear regression analysis, utilizing IBM SPSS Version 27 as the analytical tool, demonstrates that Knowledge Management, Time Management, and work motivation significantly effect Organizational Effectiveness.    Keyword: Knowledge Management, Time Management, Work Motivation, Organizational Effectiveness.